(untitled) (Research, Society and Development, 2023)
We aimed to characterize the epidemiological profile of reported cases of pesticide poisoning in the state of Sergipe between 2007 and 2021. Secondary data were obtained from the National Database of Notifiable Diseases Information System (SINAN) and National Toxicological Information System (SINITOX), through the Department of Informatics of the Unified Health System (DATASUS) and analysis performed using the free tool Google Sheets. During the studied period, 960 cases of exogenous pesticide poisoning were registered in the state. The municipality of Aracaju had the highest percentage of the number of cases. The incidence prevailed in females, in the 20-39 age group, in the brown race and among those with incomplete primary education. The most used toxic agent was rodenticide, suicide attempt predominated as a circumstance of use. Most cases resulted from a single acute exposure, confirmed by the clinical-epidemiological method, and evolved to a cure without sequelae. This study traced the epidemiological profile of the State of Sergipe with regard to the intoxication of the population and, in addition, brought little explored data and information that directly impacts policies aimed at reducing morbidity and mortality resulting from the use of pesticides.